2018
DOI: 10.1007/s00787-018-1190-4
|View full text |Cite
|
Sign up to set email alerts
|

European Multicentre Tics in Children Studies (EMTICS): protocol for two cohort studies to assess risk factors for tic onset and exacerbation in children and adolescents

Abstract: Genetic predisposition, autoimmunity and environmental factors [e.g. pre- and perinatal difficulties, Group A Streptococcal (GAS) and other infections, stress-inducing events] might interact to create a neurobiological vulnerability to the development of tics and associated behaviours. However, the existing evidence for this relies primarily on small prospective or larger retrospective population-based studies, and is therefore still inconclusive. This article describes the design and methodology of the EMTICS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 90 publications
0
54
0
Order By: Relevance
“…The fact that many patients with a clinically similar syndrome to PANDAS have no evidence of streptococcal infection, resulted in the generation of the term PANS (= Pediatric Acute-onset Neuropsychiatric Syndrome) describing a syndrome with abrupt onset of obsessive-compulsive symptoms, anxiety, and sensory symptoms in previously healthy children (19). However, results from the recently completed European-wide EMTICS study (20) failed to demonstrate evidence for a causal role of streptococcal and non-streptococcal bacteria in the onset or exacerbation of tics, but confirmed recent data for an abnormal immune responsiveness in patients with GTS with lower levels of pro-inflammatory cytokines IL-6 and TNF-α and soluble TNF-receptor as well as higher immunoglobulin levels soluble monocytes activation marker CD14 (21).…”
Section: Introductionmentioning
confidence: 76%
“…The fact that many patients with a clinically similar syndrome to PANDAS have no evidence of streptococcal infection, resulted in the generation of the term PANS (= Pediatric Acute-onset Neuropsychiatric Syndrome) describing a syndrome with abrupt onset of obsessive-compulsive symptoms, anxiety, and sensory symptoms in previously healthy children (19). However, results from the recently completed European-wide EMTICS study (20) failed to demonstrate evidence for a causal role of streptococcal and non-streptococcal bacteria in the onset or exacerbation of tics, but confirmed recent data for an abnormal immune responsiveness in patients with GTS with lower levels of pro-inflammatory cytokines IL-6 and TNF-α and soluble TNF-receptor as well as higher immunoglobulin levels soluble monocytes activation marker CD14 (21).…”
Section: Introductionmentioning
confidence: 76%
“…Participants were recruited from 16 child and adolescent psychiatry or pediatric neurology outpatient clinics, or through advertisement of the study to patient organizations and other health professionals. Exclusion criteria were having a serious medical illness, treatment with antibiotics during the last month (as the included children were also eligible to participate in a separate antibiotic study [see 22 ]), or an inability to understand and comply with the study procedures. The adolescent’s parents or legal guardians provided written informed consent and the participating adolescent provided written consent or assent in line with the local medical-ethical regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Our study sample consisted of 656 3-16 years old children and adolescents with a chronic tic disorder participating in the baseline measurement of the longitudinal European Multicenter Tics in Children Study (EMTICS). EMTICS aims to identify the role of genes, autoimmunity, and psychosocial stress on the onset and course of tics (see for a more detailed description: [22]). Participants were recruited from 16 child and adolescent psychiatry or pediatric neurology outpatient clinics, or through advertisement of the study to patient organizations and other health professionals.…”
Section: Participantsmentioning
confidence: 99%
“…An ongoing European longitudinal observational multicenter study is investigating the association of environmental (e.g. infectious agents) factors with the onset and course of tics and/or OC symptoms through the prospective observation of at-risk individuals (Schrag et al, 2018). Finally, a recent genomewide association study found genetic correlations between immune-related disorders and several psychiatric disorders, including OCD (Tylee et al, 2018).…”
Section: Immunological Factors and Early Interventionmentioning
confidence: 99%